Arsitektur Masa Pandemi: Ruang Keempat Sebagai Pemaknaan Ruang-Ruang Pada Rumah Tinggal - Sujatini, Siti; Dewi, Euis Puspita (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The recommendation the government to residents are, school and do other activities at home (work / school from home) has caused high frequency in settlement or houses activities. An increase in the frequency of activities with different kinds of the nature and type of activity in dwelling in the pandemic that has caused many changes of the meanings and functions of occupancy rooms. Occupancy very important besides serves as the residence also serves to do all activities due to exertion out occupancy is not currently allows. This report is in order to know how far the meaning change and functions of space on occupancy so that this research result can be used as a reference to the designers in designing home lives in accordance with the needs now. Methods used is the exploration and identification and grouping the activities that occurs in some dwelling houses, spaces then identification used for the activities of usually accomplished outdoors, diketahui mixing and will be of various types place, first place, two and third place, where combination some place typologies meaning as an activity to the fourth space. The result obtained is that the presence of the third and fourth not prolong the problem but in fact the occurrence of the fourth of this to solve problems and the presence of the fourth was not just for improving the economy but also for safety sake, health and comfort